The New South Africa and international news flow - Arnold de Beer; Lynnette Serfontein; Annelie Naude (Communicare)
The democratization developments in Africa during the 19905 (and not the least in South Africa) offered new opportunities for researchers in the field of news flow studies. Since the 19505, a number of studies have been undertaken internationally, but relatively few comparative studies were done in Africa since 1990. The end of the Cold War and the fall of the Berlin Wall demand not only new cartographic and conceptual maps, but also new news media maps, espeially of Africa. In this article, a broad question is posed: "How does South African mass media portray South Africa and the rest of the world in the 19905 through the process of international news coverage?' This article deals with some possible answers to this question as it pertains to specific newspapers and broadcast news in the country. The general goal was to provide answers to some of the questions set out in the international project on Global NewsFlow in the 1990s for the period 3-9 and 17-23 September 1995. Aspects such as main news topics,main news events, datelines and sources of international news were, amongst others, addressed.